Adult-onset spinocerebellar ataxia syndromes due to MTATP6 mutations. Issue 9 (10th May 2012) - Pfeffer, Gerald; Blakely, Emma L; Alston, Charlotte L; Hassani, Adam; Boggild, Mike; Horvath, Rita; Samuels, David C; Taylor, Robert W; Chinnery, Patrick F
Abstract : Background: Spinocerebellar ataxia syndromes presenting in adulthood have a broad range of causes, and despite extensive investigation remain undiagnosed in up to ∼50% cases. Mutations in the mitochondrially encoded MTATP6 gene typically cause infantile-onset Leigh syndrome and, occasionally, have onset later in childhood. The authors report two families with onset of ataxia in adulthood (with pyramidal dysfunction and/or peripheral neuropathy variably present), who are clinically indistinguishable from other spinocerebellar ataxia patients. Methods: Genetic screening study of the MTATP6 gene in 64 pedigrees with unexplained ataxia, and case series of two families who had MTATP6 mutations. Results: Three pedigrees had mutations in MTATP6, two of which have not been reported previously and are detailed in this report. These families had the m.9185T>C and m.9035T>C mutations, respectively, which have not previously been associated with adult-onset cerebellar syndromes. Other investigations including muscle biopsy and respiratory chain enzyme activity were non-specific or normal. Conclusions: MTATP6 sequencing should be considered in the workup of undiagnosed ataxia, even if other investigations do not suggest a mitochondrial DNA disorder.